PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DOSEN - M. Imam Mutttaqijn (JMB : Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine the effect of work discipline and work environment on job satisfaction at Muhammadiyah University of Tangerang lecturers. The research was conducted on lecturers at the Muhammadiyah University of Tangerang. The research method used is to use a quantitative approach, with survey methods and cross-sectional. The population size of 550 is all lecturers at the Muhammadiyah University of Tangerang. The sample size was taken 10% by 55 people. Data collection techniques using observation, interviews and questionnaires. Data analysis using simple linear regression analysis and multiple linear regression. The results showed that the variables of work discipline and work environment partially had a significant effect on the satisfaction of lecturers at Muhammadiyah University of Tangerang. And simultaneously work discipline and work environment affect the job satisfaction of lecturers at the University of Muhammadiyah Tangerang.Keywords: Work Discipline, Work Environment, and Job Satisfaction